La bsqueda de nuevos espacios para habitar - Castro Alfaro, Jose Leonardo (2020)
This Professional Sufficiency Work entitled The search for new spaces to inhabit is a proposal for a learning session in the Social Sciences Area in the Second Grade of Secondary School. This class proposal addresses the component Geographic Space, Society and Economy, whose general theme is migrations, and in particular, internal migrations. The learning session is developed from a competency-bsed approach, under the new paradigms of education. This report is composed of three parts, which are: design of the learning session, theoretical support and pedagogical support. The first part corresponds to the specific curricular aspect of the learning session. The second deals with the socio demographic phenomenon of migration, with particular emphasis on internal or national migration. The last part corresponds to the reflective theoretical scaffolding of the educational act embodied in this work.